Improving The Skill of Writing Procedure Text in Indonesian Language Learning Using Brain Writing Learning Model in Class IV Elementary School - Noviani, Rika; Suriani, Ari (Universitas Trunojoyo Madura, 2024)
This study aims to describe how the results of improving procedure teks writing skills in Indonesian language learning using Brain Writing learning model in class IV Public Elementary School 17 Manggis Ganting Koto Selayan. This type of research is classroom Action Research using qualitative and quantitative approaches. This research was conducted at Public Elementary School 17 Manggis Ganting Koto Selayan with research subject namely teachers and grade IV students. The results of this study indicate that there is an increase in 1) cycle I teaching modules with an average of 85,93% (good) and cycle II with an average score of 93,75% (very good). 2) implementation of the teacher aspect in cycle I the average score obtained was 86,36% (good) in cyle II the average score obtained was 95,45 % (veru good), implementation on the aspect of student in cycle I the average score obtained was 86,36% (good) increased in cycle II with the average score obtained was 95,45% with (veryy good) 3) the result of the assesment of student skills in cycle I with an average score of 77,02%, in cycle II by obtaining a score of 88,04 (good). Based on the result obtained, it can be concluded that the Brain Writing model can improve the skills of sriting prosecural texts in Indonesian languange learning in elementary schools